AKTIVITAS ANTIDIABETES MINUMAN HERBAL CAMPURAN DAUN EUCALYPTUS, KUNYIT DAN DAUN JAMBU BIJI - Samsu Udayana Nurdin; Diki Irawan; Subeki Subeki; Sussi Astuti (Jurusan Teknologi Hasil Pertanian, 2026)
Diabetes mellitus (DM) is a metabolic disorder characterized by high blood sugar levels in the body. The aim of this research was to study the effect of addition eucallyptus leaf in herbal beverage of a mixture of guava leaf and turmeric. The research was arranged in Randomized Complete Block Design (RCBD) with five treatments and five replications. The treatments were proportion of eucalyptus leaf in herbal beverage a mixture of guava leaf and turmeric that considered at 0%:72%:28% (C1), 5%:69%:26% (C2), 10%:66%:24% (C3), 15%:63%:22% (C4), 20%:60%:20%. The observations in this study include total flavonoid, phenol, inhibition of α-amilase enzymes activity, and sensory test. The data were analyzed for similarity of variance with Bartlett’s Test, the addition of data tasted by the Tukey’s test, then the data were analyzed by variance to determine the effect between treatments and further analyzed by the Smallest Significant Difference Test (LSD) at the level 5%. The results showed that the best treatment was the addition 20% of eucalyptus leaf, 60% of turmeric, and 20 % guava leaf, with total contain of flavonoids is an amount of 402,75 ppm (EGCE), total fhenol is an amount of 500,14 ppm (GAE), inhibition of α-amilase enzymes activity is an amount of 61,18%, and sensory test with score of 3,96 (like), aroma with score of 3,67 (like), colour with score of 3,08 (neutral), and overall acceptance with score of 4,06 (like). Total of flavonoids and phenol in herbal beverage have a positive correlation to enzyme inhibition, with the higher of total flavonoid and phenol content will increase inhibition of the α-amylase enzyme.